Influence of sublethal concentrations of antibiotics on the expression of the mannose-specific ligand of Escherichia coli. - Eisenstein, B I (1980)
The ability of streptomycin, in subinhibitory concentrations, to differentially suppress the acquisition of the mannose-binding activity of Escherichia coli was demonstrated in several strains, but not one with a ribosomal mutation to high-level streptomycin resistance, rpsL. We also determined that the growth of bacteria in other antibiotics, notably those that interfere with protein synthesis, resulted in diminished mannose-binding activity (as measured by yeast cell agglutination), degree of piliation (as measured by electron microscopy), and adherence to human oral epithelial cells. The aminoglycoside antibiotics streptomycin, gentamicin, and neomycin had the most marked effects relative to their minimum inhibitory concentrations, followed by tetracycline. Both spectinomycin and chloramphenicol had more effect on adherence than on piliation, although spectinomycin had a more pronounced effect on mannose-binding activity than did chloramphenicol. We conclude that antibiotics, at concentrations below their minimum inhibitory concentration, may have profound effects on surface properties of bacteria that may be pertinent for their ability to colonize and infect human mucosal surfaces. The mechanism(s) may vary from one drug to another, but appear to depend on the classic actions of the antibiotics on inhibiting protein synthesis.